2016
DOI: 10.1007/s11999-016-4934-9
|View full text |Cite
|
Sign up to set email alerts
|

Cement Augmentation in Sacroiliac Screw Fixation Offers Modest Biomechanical Advantages in a Cadaver Model

Abstract: Background Sacroiliac screw fixation in elderly patients with pelvic fractures is prone to failure owing to impaired bone quality. Cement augmentation has been proposed as a possible solution, because in other anatomic areas this has been shown to reduce screw loosening. However, to our knowledge, this has not been evaluated for sacroiliac screws. Questions/purposes We investigated the potential biomechanical benefit of cement augmentation of sacroiliac screw fixation in a cadaver model of osteoporotic bone, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 46 publications
2
39
0
5
Order By: Relevance
“…29 Published data from mechanical studies in cadaveric hip models are varied with cement-augmented sacroiliac screws shown to have similar to significantly higher construct stiffness and pull-out strength compared to uncemented screws. 30,31 In theory, bone union of the fracture surfaces are not jeopardized as they are spared of the cement, 29 but the long-term outcomes are uncertain due to paucity in clinical trials. A recent clinical trial demonstrated improved bone mass and reduced pedicle screw loosening with the use of teriparatide (human recombinant parathyroid hormone) for 6 months after spinal fusion compared to bisphosphonates alone.…”
Section: Discussionmentioning
confidence: 99%
“…29 Published data from mechanical studies in cadaveric hip models are varied with cement-augmented sacroiliac screws shown to have similar to significantly higher construct stiffness and pull-out strength compared to uncemented screws. 30,31 In theory, bone union of the fracture surfaces are not jeopardized as they are spared of the cement, 29 but the long-term outcomes are uncertain due to paucity in clinical trials. A recent clinical trial demonstrated improved bone mass and reduced pedicle screw loosening with the use of teriparatide (human recombinant parathyroid hormone) for 6 months after spinal fusion compared to bisphosphonates alone.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sacroiliac cement augmentation was introduced. Indeed, biomechanical examination failed to reveal the superiority of this technique in the hemipelvis model [ 33 35 ] the investigation of sole screw-sacral model yielded higher stability using augmented screws [ 36 ]. But so far, clinical trials using this technique especially regarding the outcome and pain are still sparse.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biomechanical results on the effect of augmentation are contradictory. Some authors found no difference between the augmentation of sacroiliac-screw and conventional sacroiliac-screw fixation [ 20 , 21 , 22 ]. Others report on improved biomechanical stability due to cement augmentation [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%